Finding common ground: horse riders' preferences and potential for conflict for varying management actions - Algrim, Susi J. (Kansas State University, 2017)
The need to balance increasing recreation demands with resource conservation in parks and protected areas presents a challenge for land managers. Managing recreational use of vast land and river areas often encompasses concerns about increasing numbers of recreation visitors, including horse riders. These increases in visitor use may cause adverse impacts to natural resources. A typical outdoor recreation activity, like horse riding, can lead to such impacts as soil erosion, compaction, damage to vegetation, wildlife disturbance, and water pollution. Parks and protected areas require diligent monitoring of these impacts. Along with biophysical impacts, potential social conflicts usually revolve around shared trail use with other horse riders, mountain bikers, and/or hikers. Self-administered questionnaires were given to recreationists (i.e., horse riders) at Ozark National Scenic Riverways (OZAR) in Missouri, U.S.A. Data were collected about levels and patterns of visitor activities on trails at OZAR via stratified random sample at multiple locations, times of day, days of the week and time of year (e.g. summer and fall), thus capturing a representative sample of the riders throughout the whole park. The study examined horse riders’ perceptions of potential management scenarios regarding horse riding trails. Additionally, experience use history data at OZAR were collected. The objective of the research was to explore management options when looking at seasonality, temporal differences, experiential level and the perceived severity of the actions to horse riders at OZAR. The Potential for Conflict Index was used for measuring the potential for conflict between users at different times of the week and times of year (e.g. summer and fall), as well as between horse riders and managers (through proposed management actions). This study sought to help inform park and protected area managers about horse riders’ perceptions of potential management actions and the potential for conflict related to said management actions. Of the management scenarios, there is a lower potential for conflict for trail permitting than trail management. Fall visitors had a higher potential for conflict regarding trail permitting (PCI₂ value = 0.43) and fall users also had a higher potential for conflict for trail management (PCI₂ value = 0.25). For expert and novice users, both groups felt similarly about trail conditions, trail permitting, and trail management; however, there was an overall lower potential for conflict for expert horse riders than novice horse riders. The results revealed the complexity of managing horse use in a protected area. Even during periods of high use, horse riders did not report crowded conditions, nor did horse riders favor restricting use on the trails. Additionally, horse riders felt that the trail conditions were acceptable. As past research has shown, increased horse use often leads to degraded ecological conditions (though none was perceived) and possible conflicts with other users (but not intra-activity). Limiting use may be the only viable way to maintain the ecological integrity of the park, regardless of horse riders lack of desire for restricted use or the presence of experiential impacts. Managers often have to make difficult decisions in the face of conflicting information, and this study clearly displays this dilemma.
Keywords: Outdoor recreation; Horse riding; Potential for conflict index; Natural resource management